Corrosion Behaviors of Long‐Period Stacking Ordered Structure in Mg Alloys Used in Biomaterials: A Review. Issue 7 (23rd April 2018) - Zong, Ximei; Zhang, Jinshan; Liu, Wei; Zhang, Yatong; You, Zhiyong; Xu, Chunxiang
Abstract : The long‐period stacking ordered (LPSO) phases have distinctive microstructures and significant effect on the promotion of mechanical properties of Mg alloys, which have received considerable attention not only as industrial materials but also as biodegradable implant materials recently. By now, numerous researchers devote to study the effects of the microstructures of LPSO phases on the mechanical properties of Mg alloys. But a few of them reveal the relationship between LPSO phases and corrosion behaviors of Mg alloys. Therefore, the knowledge of characteristics of LPSO phases and their effects on biocorrosion behaviors is essential. In this review, the current understanding about the structure, growth, transformation, and deformation of LPSO phases in Mg alloys are summarized. The recent developments of biocorrosion behaviors of Mg alloys are reviewed. The information on the immersion and corrosion mechanisms of Mg alloys are provided. The role of LPSO structures on corrosion behaviors of Mg alloys is intensively analyzed. Based on the current understandings, some problems are pointed out and suggestions for further research of Mg alloys with LPSO structures using as biomedical materials are provided. Abstract : Review developments about the structure, growth, transformation, and deformation of LPSO phases in Mg alloys, and the role of LPSO structures on corrosion behaviors of Mg alloys is dissected as presented in the graphic. The advances about biocorrosion properties of Mg alloys with LPSO phases are summarized.